Demographics and Epidemiology of Discoid Menisci of the Knee: Analysis of a Large Regional Insurance Database. Issue 9 (17th September 2020) - Grimm, Nathan L.; Pace, James Lee; Levy, Benjamin J.; Arthur, D'Ann; Portman, Mark; Solomito, Matthew J.; Weiss, Jennifer M.
Background: A discoid meniscus is a morphological variant of normal knee joint meniscus shape and ultrastructure that can lead to traumatic tearing of this tissue and early joint osteoarthritis. Purpose/Hypothesis: The purpose of this study was to determine the prevalence of discoid menisci in a large, ethnically diverse regional cohort and to evaluate possible risk factors. The hypothesis was that there would be no difference in the epidemiological distribution of discoid menisci based on ethnicity or sex. Study Design: Descriptive epidemiology study. Methods: The study population was from a regional, integrated health care system cohort from Kaiser Permanente of Southern California that, as of 2016, included more than 4.5 million patients. Patient demographics included age, sex, and ethnicity within this cohort. Potential risk factors analyzed included age, sex, ethnicity, and body mass index (BMI). Unique characteristics of a discoid meniscus were analyzed, including a symptomatic versus asymptomatic meniscus, location of meniscal tear and type of meniscus, and frequency of meniscal surgical treatment. Results: A total of 223 patients with a confirmed discoid meniscus were identified, yielding an overall prevalence rate of 4.88 per 100, 000 patients. Those identifying as Black had the lowest prevalence (2.68/100, 000), while Hispanic ethnicity had the highest (6.01/100, 000). However, there was no significant difference with regard to ethnicity ( P = .283), nor any significant difference between sexes. BMI did not significantly influence the rate of discoid menisci ( P = .504). A majority (77.5%) of patients were symptomatic, while 22.5% of patients with discoid menisci were asymptomatic and discovered incidentally. Symptomatic discoid menisci were more likely to be operated on compared with asymptomatic discoid menisci (71% vs 14%, respectively; P = .001; odds ratio, 14.8 [95% CI, 5.8-37.2]). Horizontal and bucket-handle tears were the more common tear types. Of the discoid menisci in this cohort, 55.6% underwent surgery, with 95.2% undergoing reported saucerization. Conclusion: In this very diverse population-based cohort of patients, there did not seem to be a significant predilection of discoid menisci with regard to ethnicity. Neither sex nor BMI significantly influenced the rate of discoid menisci. More than three-quarters of those with a diagnosed discoid meniscus were symptomatic. Of the tears that occurred with discoid menisci, horizontal and bucket-handle tears made up the largest proportion.